Vacuum effects on massive spinor fields: S-1 x R-3 topology - Tomazelli, J. L.; Costa, L. C. (Springer, 2006)
The aim of this work was to investigate the role played by an external field on the Casimir energy density for massive fermions under S-1 x R-3 topology. Both twisted- and untwisted-spin connections are considered and the calculation in a closed form is performed using an alternative approach based on the combination of the analytic regularization method and the Euler-Maclaurin summation formula. It is shown that no mass scale appears in the final result and, therefore, Casimir effect arises only from the boundary conditions and vacuum fluctuations induced by the coupling with the external field.
Keywords: casimir effect; external field quantum electrodynamics